Surgical management of haemorrhaging renal angiomyolipoma in pregnancy. (2015) - Preece, P.; Mees, B.; Norris, B.; Christie, M.; Wagner, T.; Dundee, P.
Highlights: We report the case of a 25-week pregnant woman that had a ruptured AML. This is the first case of nephrectomy in late second trimester with the foetus left in-utero. We present a literature review of the management of bleeding AML in pregnancy. Abstract: Introduction: Renal angiomyolipoma (AML) is a benign mesenchymal tumour of the kidney with a tendency of aneurysm formation at risk of rupturing. Due to increased maternal circulation and hormonal influences, rupture risk is greater in pregnancy, often leading to a vascular emergency and premature delivery or termination. Presentation of case: A 24-weeks pregnant woman (45 years old, G6P1) presented with haematuria and flank pain. CT showed AML with acute haemorrhage. The patient became haemodynamically unstable and underwent urgent embolisation and follow-on total radical nephrectomy with the foetus being left in-utero. This involved a multidisciplinary team (urologist, vascular surgeon, interventional radiologist and obstetrician). The procedure was uncomplicated and the pregnancy went to term with a healthy girl delivered at 38 weeks. Discussion: The incidence of AML is 0.13% in the general population. 21 reports of haemorrhaging AML in pregnancy have been published in the last 35 years. Mean gestational age was 29.6 weeks. Eight were treated conservatively to term, one underwent exploratory laparotomy with evacuation of haematoma only, five were embolised, and seven were managed with nephrectomy. Of the nephrectomy subgroup, one was preceded by vaginal delivery and five underwent concurrent caesarean section (one with pre-op embolisation). There were two associated foetal deaths. Conclusion: This case demonstrates that with a multidisciplinary approach, it is possible to successfully leave a foetus undelivered whilst performing a radical nephrectomy for a large bleeding AML in a woman carrying a late second trimester pregnancy.